Organisational intelligence and digital government service quality: the mediating role of occupational stress among Malaysian service providers - Ramakrishnan, Subashini (2023)
The need to evolve and transform public service has led the public to re-think its approach, and to use technological tools to improve access, efficiency and satisfaction of users. The same scenario has also been observed in the Malaysian public sector, as to how the industrial revolution and COVID-19 pandemic have forcibly led to a greater emphasis on digitalisation initiatives. Today, with more than 50% of Malaysian public services available online (end-toend), digital service quality is to be given more emphasis, as it is the most important determinant in ensuring user satisfaction. Essentially this study seeks to broaden the knowledge of digital services quality in the public sector, due to dissimilarities with the context of the private sector. Additionally, service providers' perspectives such as back-office managementrelated strategies have not been examined to a similar extent as the customers' standpoint. It is also important to note that the role of employee well-being has received very little attention in understanding its importance to service delivery performance. Following this, the study proposed four research objectives to gain a better understanding on the mediating role of occupational stress in addressing the missing link between organisational intelligence (OI) traits, and digital government service quality.